"Experience Based on a Study of Demand among Kolkhoz Workers". Issue 5 (4th July 2022) - Bakhtin, Mikhail
Abstract : "Experience Based on a Study of Demand among Kolkhoz Workers" was published under the rubric of "Shared Experience" in the journal Sovetskaya Torgovlya ("Soviet Trade") No. 3, May–June 1934. Sovetskaya Torgovlya was an organ of the Institute of Economics as part of the Communist Academy, the Central Union of Consumer Societies of the USSR and the People's Commissariat for Food Supplies of the USSR.